Enhancing the early home learning environment through a brief group parenting intervention: study protocol for a cluster randomised controlled trial. Issue 1 (December 2016) - Nicholson, Jan; Cann, Warren; Matthews, Jan; Berthelsen, Donna; Ukoumunne, Obioha; Trajanovska, Misel; Bennetts, Shannon; Hillgrove, Tessa; Hamilton, Victoria; Westrupp, Elizabeth; Hackworth, Naomi
Abstract Background The quality of the home learning environment has a significant influence on children's language and communication skills during the early years with children from disadvantaged families disproportionately affected. This paper describes the protocol and participant baseline characteristics of a community-based effectiveness study. It evaluates the effects of'smalltalk', a brief group parenting intervention (with or without home coaching) on the quality of the early childhood home learning environment. Methods/design The study comprises two cluster randomised controlled superiority trials (one for infants and one for toddlers) designed and conducted in parallel. In 20 local government areas (LGAs) in Victoria, Australia, six locations (clusters) were randomised to one of three conditions: standard care (control);smalltalk group-only program; orsmalltalk plus (group program plus home coaching). Programs were delivered to parents experiencing socioeconomic disadvantage through two existing age-based services, the maternal and child health service (infant program, ages 6–12 months), and facilitated playgroups (toddler program, ages 12–36 months). Outcomes were assessed by parent report and direct observation at baseline (0 weeks), post-intervention (12 weeks) and follow-up (32 weeks). Primary outcomes were parent verbal responsivity and home activities with child at 32 weeks. Secondary outcomes included parenting confidence, parent wellbeing and children's communication, socio-emotional and general development skills. Analyses will use intention-to-treat random effects ("multilevel") models to account for clustering. Recruitment and baseline data Across the 20 LGAs, 986 parents of infants and 1200 parents of toddlers enrolled and completed baseline measures. Eighty four percent of families demonstrated one or more of the targeted risk factors for poor child development (low income; receives government benefits; single, socially isolated or young parent; culturally or linguistically diverse background). Discussion This study will provide unique data on the effectiveness of a brief group parenting intervention for enhancing the early home learning environment of young children from disadvantaged families. It will also provide evidence of the extent to which additional one-on-one support is required to achieve change and whether there are greater benefits when delivered in the 1st year of life or later. The program has been designed for scale-up across existing early childhood services if proven effective. Trial registration 8 September 2011;ACTRN12611000965909 .